KESATUAN EROS DAN AGAPE SEBAGAI KASIH ALLAH DALAM INKARNASI - Kayaman, Margareta Florida (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2024)
Across the history of Christianity, eros, a dimension of love, is considered a love that cannot reach God or even into the love of God. This view shows that the source of eros is not God. Eros is always seen as love that is of human being, and therefore cannot be compared with agape. Based on the view, in this paper I try to show that the source of the eros is God. Eros can be aligned with agape; the unity of eros and agape can be found in God's love. The unity of dimensions of love: eros and agape, is also considered the real basis of incarnation of Christ. I developed the argument, following the Encyclical letter Deus Caritas est on perichoresis of the Trinity and elaborating some theologians' proposition on the relation between eros and agape.